“THE DEEPER INTO THE WOOD...”: RELATIONS IN THE TRIANGLE USACHINA-RUSSIA ARE INCREASINGLY GETTING UNEVEN - V. A. Kremeniuk (Сравнительная политика, 2015)
The article analyzes the evolution of relation inside the strategic triangle USSR/Russia — China — USA, which was and is the fundamental part of world order. The author reviews various configurations of cooperation and competition and bilateral relations through the lens of the interests of the parties and the US role in the triangle. The changes that took place in the component parts of the triangle fostered changes in politics and thus altered the roles and weight of the parties and of the relations between them and as a result a stalemate occurred in the triangle. The author concludes that the longer the triangular uncertainly is maintained, the more challenges will be faced by the leaders of the triangle parties.